2020
DOI: 10.2174/1389557520666200414161316
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Uses, Therapeutic Effects and Recent Advances of Curcumin: A Mini-Review

Abstract: : Studies regarding the uses and biological benefits curcumin have long been paid worldwide attention. Curcumin is a polyphenol found in the turmeric spice which is derived from the rhizomes of Curcuma longa. Curcumin is a major constituent of the traditional Indian holistic system, Ayurveda, and it is well-known in treating diverse ailments. The aim of this study is to conduct an overview that introduces the traditional uses and therapeutic effects of this valuable phytochemical with more focus on the antitum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…None of the nutraceuticals were effective in preventing uranium-induced metabolic viability decreases in Caco-2 cells. It is not known whether the “rescue effect” is due to the metal-binding capabilities of the tested nutraceutical or their reported antioxidant properties [ 29 , 30 , 31 ]. In addition, the ability of the nutraceuticals to induce the expression of proteins that may function in the protection and/or repair of metal-induced damage cannot be overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…None of the nutraceuticals were effective in preventing uranium-induced metabolic viability decreases in Caco-2 cells. It is not known whether the “rescue effect” is due to the metal-binding capabilities of the tested nutraceutical or their reported antioxidant properties [ 29 , 30 , 31 ]. In addition, the ability of the nutraceuticals to induce the expression of proteins that may function in the protection and/or repair of metal-induced damage cannot be overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decades, there has been a surge of interest in curcumin as evidence about its efficacy in a wide variety of diseases is growing, including cardiovascular, autoimmune, and neurodegenerative diseases as well as diabetes and cancers (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, HGF enhances the migration and invasive capacity of tumor cells [ 4 , 24 ]. Curcumin has been shown to exert antitumor effects in various tumors [ 18 , 33 , 34 ]. It induces tumor cell apoptosis and inhibits tumor cell proliferation, growth, invasion, and anti-inflammation [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of curcumin, used alone or in combination with other agents, has been evaluated in various clinical trials involving various diseases, including cancer, rheumatoid arthritis, Alzheimer's disease, diabetes, and leukoderma, among others [ 44 ]. Curcumin has been shown to block aggressive cancer progression by modulating various signaling pathways [ 34 ]. In this study, we found that curcumin suppressed HGF-induced migration, invasion, and EMT by inhibiting the c-MET/PI3K/Akt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%